2013
DOI: 10.1091/mbc.e12-12-0881
|View full text |Cite
|
Sign up to set email alerts
|

The nucleolus stress response is coupled to an ATR-Chk1–mediated G2 arrest

Abstract: HeLa cells engineered with the fluorescent ubiquitinylation-based cell cycle indicator are used to study the connection between nucleolar stress and cell cycle progression. The results demonstrate a feedforward mechanism that leads to G2 arrest and identify ATR and Chk1 as molecular agents of the requisite checkpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 37 publications
3
37
1
Order By: Relevance
“…Interestingly, recent studies reported a p53-independent nucleolar stress response activated by Pol I inhibition involving the Wnttarget Peter Pan, nucleophosmin, Bax, and ATM/ATR signaling in the absence of global DNA damage. [26][27][28] Here, we demonstrate that ATM/ATR signaling contributes directly to the therapeutic efficacy of Pol I inhibition in the absence of p53.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, recent studies reported a p53-independent nucleolar stress response activated by Pol I inhibition involving the Wnttarget Peter Pan, nucleophosmin, Bax, and ATM/ATR signaling in the absence of global DNA damage. [26][27][28] Here, we demonstrate that ATM/ATR signaling contributes directly to the therapeutic efficacy of Pol I inhibition in the absence of p53.…”
Section: Discussionmentioning
confidence: 64%
“…Among the cellular pathways involved in cellular stress responses, we explored the involvement of three different kinases, that could be implicated in p53 phosphorylation, namely checkpoint kinase 1 (Chk1), checkpoint kinase 2 (Chk2) and p38 mitogen activated protein kinase (p38 MAPK). Chk1 and p38 MAPK kinases have been implicated in cellular responses to ribosomal stress thereby being good candidates for our purposes . Chk2, however, has been linked to DNA damage responses, but to our knowledge nobody has ever observed its activation in ribosomal stress so far.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the target genes are involved in both G1/S (CCNE1, CDK2, CCND1, CDK4, CDK6, and CDKN2C (p18/INK4c)) and G2/M (CDC25A, Wee1) control. It should be noted that Chek1 regulates both intra-S and G2/M checkpoints [41, 42]. Thus, it can be concluded that the majority of pa-miRNA's target genes are involved in the regulation of cell cycle checkpoints and cell cycle progression.…”
Section: Resultsmentioning
confidence: 99%